2022
DOI: 10.1007/s00784-022-04826-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of customized CAD/CAM abutments on cytokine levels in peri-implant crevicular fluid during early implant healing: a pilot study

Abstract: Objectives This study aimed to assess levels of biomarkers associated with inflammation and tissue destruction in peri-implant crevicular fluid (PICF) of implants provided with customized or standard healing abutments during early implant healing. Materials and methods Thirty implants were placed in 22 patients with partial posterior edentulism. Subsequently, test group implants (n=15) received one-piece titanium abutments that were fabricated using comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Levels of biomarkers linked to tissue damage and inflammation were measured in peri-implant crevicular fluid (PICF) during initial implant healing, one week after delivery of the crown, at three months, and at six months. They found that throughout the observation period, MMP-13 levels rose whereas CRP, TGF-β, IL-1β, IL-6, IL-8, MIP-1a, osteopontin, and osteoactivin protein expression significantly declined [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Levels of biomarkers linked to tissue damage and inflammation were measured in peri-implant crevicular fluid (PICF) during initial implant healing, one week after delivery of the crown, at three months, and at six months. They found that throughout the observation period, MMP-13 levels rose whereas CRP, TGF-β, IL-1β, IL-6, IL-8, MIP-1a, osteopontin, and osteoactivin protein expression significantly declined [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…After duplicate removal and title/abstract screening, 19 articles were selected for full-text analysis. Hence, 13 studies were excluded for the following reasons: the aim of the study was inconsistent with the aim of the systematic review [16,[26][27][28][29][30][31][32][33][34][35], overlapping data/same cohort [36] and the study design was inconsistent with the inclusion criteria [37]. The reasons for exclusion are available in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%